Antistatic composite material based on ultra-high molecular weight polyethylene
By adding functional additives to the ultra-high molecular weight polyethylene composite material, the alkenyl group in the modified polypyrrole structure forms a conductive path with graphene, and the antibacterial properties are enhanced through the electrostatic attraction of the quaternary ammonium salt, the electrostatic and antibacterial problems of the ultra-high molecular weight polyethylene composite material are solved, and excellent antistatic and antibacterial effects are achieved.
Patent Information
- Application Number
- CN202411923978.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-02-25
AI Technical Summary
Ultra-high molecular weight polyethylene composite materials are prone to static electricity in dry, low-humidity environments and when they are in contact with charged objects with friction, and have poor antibacterial properties and are easily eroded by bacteria.
By doping quaternary ammonium salt modifications in pyrrole monomers, a substitution reaction of secondary amino groups in the modified polypyrrole structure and halogen in the halogen alkenyl modifier structure is obtained to obtain functional additives, and it is mixed with ultra-high molecular weight polyethylene, polypropylene, coffee grounds, antioxidants, crosslinking agents, lubricants, graphene and other raw materials in a high mixer. After melt extrusion granulation and foaming treatment, an antistatic composite material is prepared.
By forming a stable and tight conductive pathway and strong electrostatic attraction, the composite material exhibits excellent antistatic and antibacterial properties, avoiding static accumulation and bacterial erosion, and prolonging service life.
Smart Images

Figure CN119505404A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, and in particular to an antistatic composite material based on ultra-high molecular weight polyethylene. Background Art
[0002] Polyethylene is one of the most widely used plastic materials at present. It has many advantages, such as light weight, excellent tolerance to chemical substances, relatively low price, and good electrical insulation. Ultra-high molecular weight polyethylene is a polyethylene material with a large molecular weight and superior performance. It is used in many fields, such as packaging materials, household goods, industrial pipes, aerospace, electronics and electrical, medical, and clothing and footwear. Ultra-high molecular weight polyethylene composites have excellent wear resistance and are safe and non-toxic. However, ultra-high molecular weight polyethylene also has shortcomings. On the one hand, because the molecular weight is very high, the molecular chains are entangled with each other, which will cause the charge to be transferred between the molecular chains unsmoothly, and it is not easy to flow inside the material, which is easy to form static electricity accumulation. In a dry, low-humidity environment and when it is rubbed and in contact with charged objects, the surface charge of ultra-high molecular weight polyethylene is unbalanced, and static electricity will also be generated. The generation of static electricity in the electronics manufacturing and semiconductor industries may cause product failure or performance degradation; on the other hand, ultra-high molecular weight polyethylene materials have poor antibacterial properties and are easily corroded by bacteria during use, which has adverse effects on composite materials. Therefore, it is urgent to modify ultra-high molecular weight polyethylene composites.
[0003] In the prior art, conductive inorganic substances such as graphene, carbon nanotubes, etc. are generally added as antistatic agents. The patent with publication number CN109796545B discloses a method for preparing antistatic ultra-high molecular weight polyethylene, and antistatic ultra-high molecular weight polyethylene is obtained by adding an inorganic composition of graphene and carbon nanotubes; the patent with publication number CN104974367B discloses a method for preparing an antistatic polypropylene foam plate or sheet, and a polypropylene foam material with antistatic effect is obtained by adding carbon nanotubes as an antistatic agent. However, it is difficult to form a complete conductive path in the material by only adding conductive inorganic substances, which affects the antistatic performance. Therefore, the present invention provides an antistatic composite material based on ultra-high molecular weight polyethylene, which has excellent antistatic and antibacterial properties and can be applied to insole products. Summary of the invention
[0004] In order to solve the problems mentioned in the background technology, the object of the present invention is to provide an antistatic composite material based on ultra-high molecular weight polyethylene.
[0005] The purpose of the present invention can be achieved through the following technical solutions: An antistatic composite material based on ultra-high molecular weight polyethylene comprises the following raw materials in parts by weight: 50-70 parts of ultra-high molecular weight polyethylene, 10-20 parts of polypropylene, 5-10 parts of coffee grounds, 0.5-2.5 parts of antioxidant, 0.5-1.5 parts of cross-linking agent, 0.3-1 parts of lubricant, 5-10 parts of foaming agent, 1-3 parts of graphene and 3-6 parts of functional additives.
[0006] Furthermore, the antioxidant is antioxidant 1010 or antioxidant 168; the cross-linking agent is dicumyl peroxide or di-tert-butyl peroxycumene; the lubricant is calcium stearate or zinc stearate; and the foaming agent is azodicarbonamide or sodium bicarbonate.
[0007] Furthermore, the preparation method of the functional additive comprises the following steps: Step A: After adding pyrrole and quaternary ammonium salt modification to deionized water and stirring them evenly, the system is placed in a 0°C ice water bath, and ammonium persulfate is slowly added. After reacting for 8-10 hours, the mixture is allowed to stand for precipitation, the product is separated, and washed to obtain modified polypyrrole; Step B: Add the modified polypyrrole to N,N-dimethylformamide, stir evenly, introduce nitrogen, add the halogen olefinic modifier and catalyst, raise the temperature to 70-85°C, react for 4-5 hours, cool and discharge the material to obtain a functional additive.
[0008] By adopting the above technical scheme, a quaternary ammonium salt modifier is doped into a pyrrole monomer to obtain a modified polypyrrole, and under the action of a catalyst, a secondary amino group in the modified polypyrrole structure is substituted with a halogen in the halogen alkenyl modifier structure, thereby introducing an alkenyl group into the modified polypyrrole structure to obtain a functional additive.
[0009] Furthermore, in step A, the quaternary ammonium salt modifier is (2,3-dihydroxypropyl)trimethylammonium chloride or (3-chloro-2-hydroxypropyl)trimethylammonium chloride.
[0010] Furthermore, in step B, the halogen alkenyl modifier is any one of 2-bromopropylene, 3-bromopropylene or 3-bromo-2-methylpropylene.
[0011] Furthermore, in step B, the catalyst is any one of sodium carbonate, potassium carbonate or sodium hydroxide.
[0012] Furthermore, the preparation method of the composite material comprises the following steps: Step 1: adding ultra-high molecular weight polyethylene, polypropylene, coffee grounds, antioxidant, cross-linking agent, lubricant, graphene, and functional additives into a high-speed mixer, stirring at a stirring rate of 200-400 r / min for 1-3 hours to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 110-130° C. and the screw speed is 100-200 r / min to obtain a masterbatch; Step 3: Add a foaming agent to the masterbatch, mix evenly, and then foam and cool to shape to obtain a composite material.
[0013] Furthermore, in step three, the foaming temperature is 180-220° C., the pressure is 10-20 MPa, and the time is 10-15 min.
[0014] Beneficial effects of the present invention: The functional additive prepared by the invention has excellent electrical conductivity and also contains quaternary ammonium salt with broad-spectrum and high-efficiency antibacterial performance. On the one hand, the functional additive contains alkenyl in its structure, which can generate crosslinking with a base material under the action of a crosslinking agent to form a polymer network structure, improve the conductive network, fill in the gaps in the graphene, form a stable and tight conductive path, ensure the continuity of the conductive path, avoid disconnection of the conductive path, further improve the antistatic performance of the composite material, and achieve the effect of showing excellent antistatic performance by adding a small amount of graphene; on the other hand, the quaternary ammonium salt in the functional additive can change the permeability of the cell membrane through strong electrostatic attraction and the action with the hydrophilic group of bacteria, generate a lytic effect to damage the cell structure, and cause the cells to lyse and apoptosis, thereby giving the composite material excellent antibacterial performance, and also reducing the probability of precipitation of antibacterial substances in the composite material during long-term use, ensuring that the composite material can be antibacterial for a long time, avoiding corrosion of the composite material by bacteria, and extending the service life of the composite material.
[0015] Of course, any product implementing the present invention does not necessarily need to achieve all of the advantages described above at the same time. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the accompanying drawings required for describing the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other accompanying drawings can be obtained based on these accompanying drawings without paying creative work.
[0017] Figure 1 This is the infrared spectrum of the functional additive of the present invention. DETAILED DESCRIPTION
[0018] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0019] The preparation methods of the functional additives in the following examples and comparative examples are as follows: Preparation of functional additives Step A: 2.6 g of pyrrole and 1.5 g of (3-chloro-2-hydroxypropyl)trimethylammonium chloride were added to deionized water and stirred thoroughly, then the system was placed in an ice water bath at 0°C, 2.2 g of ammonium persulfate was slowly added, and after reacting for 8 hours, the mixture was allowed to stand for precipitation, the product was separated, and washed to obtain modified polypyrrole; Step B: Add 3.5 g of modified polypyrrole to N,N-dimethylformamide, stir evenly, introduce nitrogen, add 1.4 g of 3-bromopropylene and 0.3 g of potassium carbonate, raise the temperature to 80°C, react for 5 hours, cool and discharge the material to obtain a functional additive.
[0020] Infrared testing of functional additives, such as Figure 1 As shown, analysis shows that 3422cm -1 The absorption peak of NH in polypyrrole appears at 3048 cm -1 The absorption peak of CH in the carbon-carbon double bond appears at 2930 cm -1 and 2883cm -1 The absorption peaks of CH in methyl and methylene appeared at 1653 cm -1 The absorption peak of C=N in the pyrrole ring appeared at 1548 cm -1 The absorption peak of C=C in the pyrrole ring appeared at 1485 cm -1 The absorption peak of CN appears at . Example 1
[0021] Preparation of composite materials Step 1: Add 50g ultra-high molecular weight polyethylene, 10g polypropylene, 5g coffee grounds, 0.5g antioxidant 1010, 0.5g dicumyl peroxide, 0.3g zinc stearate, 1g graphene, and 3g functional additives into a high-speed mixer, and stir at a stirring rate of 200r / min for 1h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 110° C. and the screw speed is 100 r / min to obtain a masterbatch; Step 3: Add 5g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 180°C, a pressure of 10MPa, and a time of 10min. Then cool and shape it to obtain a composite material. Example 2
[0022] Preparation of composite materials Step 1: Add 60g ultra-high molecular weight polyethylene, 14g polypropylene, 6g coffee grounds, 0.5g antioxidant 1010, 1g dicumyl peroxide, 0.5g zinc stearate, 2g graphene, and 4g functional additives into a high-speed mixer, and stir at a stirring rate of 300r / min for 2h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 120° C. and the screw speed is 150 r / min to obtain a masterbatch; Step 3: Add 6 g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 200° C., a pressure of 15 MPa, and a time of 12 min. Then cool and shape it to obtain a composite material. Example 3
[0023] Preparation of composite materials Step 1: Add 65g ultra-high molecular weight polyethylene, 16g polypropylene, 8g coffee grounds, 1.5g antioxidant 1010, 1.5g dicumyl peroxide, 0.8g zinc stearate, 3g graphene, and 5g functional additives into a high-speed mixer, and stir at a stirring rate of 400r / min for 3h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 130° C. and the screw speed is 200 r / min to obtain a masterbatch; Step 3: Add 8g of azodicarbonamide to the masterbatch, mix well, and then foam at a temperature of 210°C, a pressure of 18MPa, and a time of 15min. Then cool and shape to obtain a composite material. Example 4
[0024] Preparation of composite materials Step 1: Add 70g ultra-high molecular weight polyethylene, 20g polypropylene, 10g coffee grounds, 2.5g antioxidant 1010, 1.5g dicumyl peroxide, 1g zinc stearate, 3g graphene, and 6g functional additives into a high-speed mixer, and stir at a stirring rate of 400r / min for 3h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 130° C. and the screw speed is 200 r / min to obtain a masterbatch; Step 3: Add 10g of azodicarbonamide to the masterbatch, mix well, and then foam at a temperature of 220°C, a pressure of 20MPa, and a time of 15min. Then cool and shape to obtain a composite material.
[0025] Comparative Example 1 Preparation of composite materials Step 1: Add 60 g of ultra-high molecular weight polyethylene, 14 g of polypropylene, 6 g of coffee grounds, 0.5 g of antioxidant 1010, 1 g of diisopropyl peroxide, 0.5 g of zinc stearate, 2 g of graphene, and 4 g of (3-chloro-2-hydroxypropyl)trimethylammonium chloride into a high-speed mixer, and stir at a stirring rate of 300 r / min for 2 h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 120° C. and the screw speed is 150 r / min to obtain a masterbatch; Step 3: Add 6 g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 200° C., a pressure of 15 MPa, and a time of 12 min. Then cool and shape it to obtain a composite material.
[0026] Comparative Example 2 Preparation of composite materials Step 1: Add 60g ultra-high molecular weight polyethylene, 14g polypropylene, 6g coffee grounds, 0.5g antioxidant 1010, 1g dicumyl peroxide, 0.5g zinc stearate, 2g graphene, and 4g polypyrrole into a high-speed mixer, and stir at a stirring rate of 300r / min for 2h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 120° C. and the screw speed is 150 r / min to obtain a masterbatch; Step 3: Add 6 g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 200° C., a pressure of 15 MPa, and a time of 12 min. Then cool and shape it to obtain a composite material.
[0027] Comparative Example 3 Preparation of composite materials Step 1: Add 60g ultra-high molecular weight polyethylene, 14g polypropylene, 6g coffee grounds, 0.5g antioxidant 1010, 1g dicumyl peroxide, 0.5g zinc stearate, 2g graphene, and 4g modified polypyrrole into a high-speed mixer, and stir at a stirring rate of 300r / min for 2h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 120° C. and the screw speed is 150 r / min to obtain a masterbatch; Step 3: Add 6 g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 200° C., a pressure of 15 MPa, and a time of 12 min. Then cool and shape it to obtain a composite material.
[0028] Comparative Example 4 Preparation of composite materials Step 1: Add 60g ultra-high molecular weight polyethylene, 14g polypropylene, 6g coffee grounds, 0.5g antioxidant 1010, 1g dicumyl peroxide, 0.5g zinc stearate, and 2g graphene into a high-speed mixer, and stir at a stirring rate of 300r / min for 2h to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 120° C. and the screw speed is 150 r / min to obtain a masterbatch; Step 3: Add 6 g of azodicarbonamide to the masterbatch, mix well, and then foam it at a temperature of 200° C., a pressure of 15 MPa, and a time of 12 min. Then cool and shape it to obtain a composite material.
[0029] Performance Testing The composite materials prepared in Examples 1 to 4 and Comparative Examples 1 to 4 were prepared into samples that met the test specifications. The surface resistivity of the samples was tested with reference to the standard GB / T 31838.3-2019 to determine the antistatic properties of the composite materials. After the samples were placed for 3 months, the antibacterial properties of the samples were tested using the following method: 1 mL of a 10 -5 The Escherichia coli liquid with CFU / mL was dropped on the surface of the sterilized sample and cultured at 37℃ and relative humidity greater than 90% for 10 hours. Then 25μL of the cultured liquid was evenly spread on the surface of the solid culture medium. After cultured at 37℃ and relative humidity greater than 90% for 24 hours, the number of colonies on the surface of the culture medium was counted and recorded as C. A blank test was also performed and the number of colonies was counted as D. Using the formula antibacterial rate (%) = [(DC) / D] × 100%, the test results are shown in the following table:
[0030] As can be seen from the above table, the composite materials prepared by Examples 1 to 4 of the present invention have excellent antistatic and antibacterial properties. Comparative Example 1 adds (3-chloro-2-hydroxypropyl) trimethylammonium chloride. After the sample is placed, (3-chloro-2-hydroxypropyl) trimethylammonium chloride is precipitated, so the antibacterial rate is poor and it is not doped into the polypyrrole material, and a complete conductive path cannot be formed in the composite material, so the antistatic performance is poor; Comparative Example 2 adds polypyrrole, fails to form a complete conductive path, and the antistatic performance is worse than that of the embodiment, and the antibacterial performance is poor; Comparative Example 3 adds modified polypyrrole, the antistatic performance is worse than that of the embodiment, and the antibacterial performance is excellent; Comparative Example 4 does not add functional additives, and the test results are all poor.
[0031] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the concept of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
Claims
1. An antistatic composite material based on ultra-high molecular weight polyethylene, characterized in that: The invention comprises the following raw materials in parts by weight: 50-70 parts of ultra-high molecular weight polyethylene, 10-20 parts of polypropylene, 5-10 parts of coffee grounds, 0.5-2.5 parts of antioxidant, 0.5-1.5 parts of cross-linking agent, 0.3-1 parts of lubricant, 5-10 parts of foaming agent, 1-3 parts of graphene and 3-6 parts of functional additives.
2. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 1, characterized in that: The antioxidant is antioxidant 1010 or antioxidant 168; the cross-linking agent is dicumyl peroxide or di-tert-butyl peroxycumene; the lubricant is calcium stearate or zinc stearate; and the foaming agent is azodicarbonamide or sodium bicarbonate.
3. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 1, characterized in that: The preparation method of the functional additive comprises the following steps: Step A: After adding pyrrole and quaternary ammonium salt modification to deionized water and stirring them evenly, the system is placed in a 0°C ice water bath, and ammonium persulfate is slowly added. After reacting for 8-10 hours, the mixture is allowed to stand for precipitation, the product is separated, and washed to obtain modified polypyrrole; Step B: Add the modified polypyrrole to N,N-dimethylformamide, stir evenly, introduce nitrogen, add the halogen olefinic modifier and catalyst, raise the temperature to 70-85°C, react for 4-5 hours, cool and discharge the material to obtain a functional additive.
4. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 3, characterized in that: In step A, the quaternary ammonium salt modifier is (2,3-dihydroxypropyl)trimethylammonium chloride or (3-chloro-2-hydroxypropyl)trimethylammonium chloride.
5. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 3, characterized in that: In step B, the halogen alkenyl modifier is any one of 2-bromopropylene, 3-bromopropylene or 3-bromo-2-methylpropylene.
6. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 3, characterized in that: In step B, the catalyst is any one of sodium carbonate, potassium carbonate or sodium hydroxide.
7. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 1, characterized in that: The preparation method of the composite material comprises the following steps: Step 1: adding ultra-high molecular weight polyethylene, polypropylene, coffee grounds, antioxidant, cross-linking agent, lubricant, graphene, and functional additives into a high-speed mixer, stirring at a stirring rate of 200-400 r / min for 1-3 hours to obtain a mixed base material; Step 2: Add the mixed base material into a twin-screw extruder, and perform melt extrusion granulation, wherein the extrusion temperature is 110-130° C. and the screw speed is 100-200 r / min to obtain a masterbatch; Step 3: Add a foaming agent to the masterbatch, mix evenly, and then foam and cool to shape to obtain a composite material.
8. The antistatic composite material based on ultra-high molecular weight polyethylene according to claim 7, characterized in that: In step three, the foaming temperature is 180-220° C., the pressure is 10-20 MPa, and the time is 10-15 min.
Citation Information
Patent Citations
A kind of preparation method of antistatic polypropylene foam board or sheet
CN104974367B
A method for preparing antistatic ultra-high molecular weight polyethylene
CN109796545B
Antistatic flame-retardant ultra high molecular weight polyethylene composition and preparation method thereof
CN102432939A
Polypropylene composite material and preparation method thereof
CN111944240A
Graphene modified ultra-high molecular weight polyethylene and preparation method thereof
CN111995811A